Pengembangan Media Pembelajaran Interaktif untuk Pengenalan OpenGL pada Mata Kuliah Grafika Komputer - Faris Afif Nababan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study focuses on the development of an interactive learning media for introducing OpenGL in the Computer Graphics course. The research approach used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The final product of this study is an interactive learning application that covers basic OpenGL material, simple programming exercises, evaluation quizzes, and other supporting information. The trial results show positive feedback from students. Based on the questionnaire analysis, the aspects of appearance, content, interactivity, and benefits received an average score of 85% in the